Controls on the architectural evolution of deep-water channel overbank sediment wave fields: insights from the Hikurangi Channel, offshore New Zealand. Issue 1 (2nd January 2022) - Tek, Daniel E.; McArthur, Adam D.; Poyatos-Moré, Miquel; Colombera, Luca; Allen, Charlotte; Patacci, Marco; McCaffrey, William D.
ABSTRACT: Deep-water channels can be bound by overbank deposits, resulting from overspilling flows, which are often ornamented with sediment waves. Here, high-resolution bathymetry, backscatter, and 2D and 3D seismic data are integrated to discern the controls on flow processes on the overbank areas of the Hikurangi Channel. Qualitative seismic interpretation and quantitative analyses of sediment wave morphologies and distributions are conducted through the shallowest 600 m of stratigraphy up to the seafloor. Four outer-bend wave fields are present throughout the studied stratigraphy on the landward margin (left margin looking down-channel) only. Originally closely spaced or combined, these fields evolved to become spatially separated; two of the separate wave fields became further subdivided into distinct outer- and inner-bend fields, whose constituent waves developed distinct differences in morphology and distribution. Sediment wave character is used to interpret the direction and strength of overbank flow. Nine controls on such flow and associated deposition are identified: flow versus conduit size, overbank gradient, flow tuning, Coriolis forcing, contour current activity, flow reflection, centrifugal forcing, interaction with externally derived flows, and interaction of overspill from different locations. Their relative importance may vary across parts of overbank areas, both spatially and temporally, controlling wave field development such that: (1) outer-bend wave fields only develop on the landward margin; (2) the influence of centrifugal force on outer-bend overbanks has increased through time, accompanying a general increase in channel sinuosity; (3) inner-bend wave fields on the landward margin form by the interaction of Coriolis-enhanced inner-bend overbank flow, and outer-bank flow from up-channel bends; (4) inner-bend fields on the oceanward margin form by the interaction of axial flow through wave troughs, and a transverse, toward-channel flow component. This work has implications for interpreting overbank flow from seafloor and seismic data, and for palaeogeographic reconstructions from outcrop data.